Multiple E-Learning technologies on practicing TOEFL structure and written expression - Pratiwi, Damar Isti; Atmaja, Dadang Sanjaya; Prasetya, Henry Widya (JEES (Journal of English Educators Society), 2021)
The present study investigates how to implement multiple e-learning technologies on practicing TOEFL PBT Section 2, Structure and Written Expression, and its effectiveness. It is a case study at Indonesian Railway Polytechnic. The participants were 48 students of the Railway Mechanical Technology program observed during eight online TOEFL practising classes. The data were collected using observation note to describe the implementation of e-learning technologies, comparing each score to determine the effectiveness of the technologies and a questionnaire to identify students’ feedback. The findings identified how to implement multiple e-learning technologies on practicing TOEFL PBT Section 2 in which effective to increase students’ TOEFL score; those technologies were regarded as interesting media on practicing TOEFL structure and written expression and received more positive feedbacks than the drawback from the students of Railway Mechanical Technology program. These imply that implementing multiple e-learning technologies on practicing TOEFL structure and written expression enhances students’ learning outcomes. HIGHLIGHTS: Multiple e-learning technologies enhance students’ learning outcomes in TOEFL PBT Section 2, structure and written expression. Quizizz, Kahoot!, Socrative, and Google Forms are interesting media on practicing TOEFL Structure and Written Expression. The fourth e-learning technologies receive more positive feedbacks than the drawback from the students in on practicing TOEFL PBT section 2.